Significant Neutrophilic Emperipolesis in Squamous Cell Carcinoma - Seza Tetikkurt; Faruk Taş; Funda Emre; Şule Özsoy; Zeki Tolga Bilece (Case Reports in Oncological Medicine)
A 53-year-old man was admitted for tooth mobility. A mass was identified at the tooth base by CT. Histopathology of the excisional biopsy revealed a moderately differentiated squamous cell carcinoma. Many intact neutrophils were observed within the malignant cell cytoplasm. The patient underwent partial maxillectomy and bilateral neck dissection. Significant neutrophilic emperipolesis was detected in the resected material. Four tumor recurrences developed in the head and neck region during follow-up. Surgery and chemoradiotherapy was performed. The latest tumor recurrence occurred in the peripharyngeal and the posterior parotideal region. The patient was started on pembrolizumab therapy and nearly complete treatment response occurred. Pembrolizumab was discontinued due to the adrenal insufficiency and pulmonary tuberculosis that developed as a treatment side effect. Pembrolizumab was commenced again when tumor recurrence occurred. The patient is currently alive with ongoing pembrolizumab and antituberculous treatment. We present this case to remark the presence of a significant neutrophilic emperipolesis in the squamous cell carcinoma of the hard palate and maxilla which is rarely encountered. Emperipolesis may predict tumor behavior and the consequences of immune-modulating treatment response in squamous cell carcinomas of the head and neck in regard to the findings of our case.